Non-binary low-density parity-check codes for the q-ary erasure channel - Garrammone, Giuliano; Paolini, Enrico; Matuz, Balazs; Liva, Gianluigi; Chiani, Marco (2013 IEEE International Conference on Communications (ICC), 2013)
The finite-length design of non-binary low-density parity-check (LDPC) codes for the q-ary erasure channel under maximum a posteriori (MAP) decoding is addressed. A low-complexity MAP decoding algorithm is reviewed for which a code design strategy is proposed. In particular, it is illustrated how a judicious code design permits to find a trade-off between performance in terms of codeword error rate (CER) and decoding complexity. As an example, the performance curve of a short (400, 200) code on the memoryless 4-ary erasure channel tightly approaches the Singleton bound at least down to a CER of 10 -8 .